Development of a Food Composition Database for Assessing Nitrate and Nitrite Intake from Animal‐based Foods. Issue 1 (3rd December 2021) - Zhong, Liezhou; Liu, Alex H.; Blekkenhorst, Lauren C.; Bondonno, Nicola P.; Sim, Marc; Woodman, Richard J.; Croft, Kevin D.; Lewis, Joshua R.; Hodgson, Jonathan M.; Bondonno, Catherine P.
Abstract : Scope: Nitrate and nitrite are approved food additives in some animal‐based food products. However, nitrate and nitrite in foods are strictly regulated due to health concerns over methaemoglobinaemia and the potential formation of carcinogenic nitrosamines. In contrast, plants (like leafy vegetables) naturally accumulate nitrate ions; a growing body of research reveals beneficial metabolic effects of nitrate via its endogenous conversion to nitric oxide. To refine the association of dietary nitrate and nitrite intake with health outcomes, reliable measures of nitrate and nitrite intake from dietary food records are required. While a vegetable nitrate content database has been developed, there is a need for a comprehensive up‐to‐date nitrate and nitrite content database of animal‐based foods. Methods and Results: A systematic literature search (1980–September 2020) on the nitrate and nitrite content of animal‐based foods is carried out. Nitrate and nitrite concentration data and other relevant information are extracted and compiled into a database. The database contains 1921 entries for nitrate and 2077 for nitrite, extracted from 193 publications. The highest median nitrate content is observed in chorizo (median [IQR]; 101.61 [60.05–105.93] mg kg ‐1 ). Canned fish products have the highest median nitrite level (median [IQR]; 20.32 [6.16–30.16] mg kg ‐1 ). By subgroup, the median nitrate value in industrial processed meat products (e.g., uncured burger, patties and sausages), whole milk powder and in particular red meat are higher than cured meat products. Processed meat products from high‐income regions have lower median nitrate and nitrite content than those of middle‐income regions. Conclusion: This database can now be used to investigate the associations between nitrate and nitrite dietary intake and health outcomes in clinical trials and observational studies. Abstract : A comprehensive nitrate and nitrite content database of animal‐based foods has been developed. The database includes nitrate and nitrite concentration data (3998 entries in total) published from 1980 to September 2020. The standardization and improved estimation of nitrate and nitrite intake will enable the investigation of nitrate/nitrite‐health outcome relationships in both observational studies and randomized controlled trials.